CNT conductive heating film and preparation method and application thereof
By performing amino modification and multi-layer coating on graphitized carbon nanotubes, modified graphitized carbon nanotubes were prepared, which solved the problem of poor agglomeration and dispersion of graphitized carbon nanotubes in the conductive heating film, significantly improved the heating performance, and was suitable for warm-keeping products.
Patent Information
- Application Number
- CN202510254485.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The agglomeration and dispersion of graphitized carbon nanotubes in existing conductive heating films lead to poor heating performance.
The graphitized carbon nanotubes were modified by ethylenediamine, and the carboxymethyl chitosan was cross-linked and coated onto the surface of the graphitized carbon nanotube with 1,2,7,8-diepoxide as cross-linking agent to form a first cladding layer, and then the second cladding layer was constructed by in-situ polymerization, and the modified graphitized carbon nanotubes were mixed with organic resin polymer to prepare a conductive heating film.
It effectively solves the agglomeration and dispersion problems of graphitized carbon nanotubes, significantly improves the heating performance of the conductive heating film, making it more suitable for warm-insulating products.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of conductive heating films, and in particular relates to a CNT conductive heating film and a preparation method and application thereof. Background Art
[0002] Conductive heating film is a type of thin film material that can generate heat when electricity is applied. It is widely used in various fields due to its many advantages such as high heating efficiency and good safety. Among them, the heating performance of the conductive heating film depends to a large extent on the inorganic filler added to it, and carbon nanotubes, namely CNTs, are a one-dimensional quantum material with a special structure. Due to its excellent electrical properties, the inorganic fillers added to the conductive heating film are often mainly carbon nanotubes. However, these conductive heating films with added carbon nanotubes still have certain disadvantages that limit their actual application effects. This is because the heating performance of ordinary carbon nanotubes still has a lot of room for improvement. Although many existing technologies will choose graphitized carbon nanotubes to replace ordinary carbon nanotubes in order to obtain better heating performance, graphitized carbon nanotubes are essentially inorganic particles, and the agglomeration phenomenon is very obvious, and the dispersion is not good, and it is ultimately difficult to play the desired effect. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a CNT conductive heating film and a preparation method and application thereof. The present invention creatively uses ethylenediamine to perform amino surface modification on the graphitized carbon nanotubes pretreated with hydrochloric acid to obtain component A, and then uses 1,2,7,8-diepoxyoctane as a cross-linking agent. Based on the bonding action of the epoxy group and the amino group, the carboxymethyl chitosan containing the amino group is cross-linked and coated on the surface of component A to form a first coating layer. Subsequently, aniline is added as a modifier, and a second coating layer is constructed based on in situ polymerization to obtain modified graphitized carbon nanotubes. The modified graphitized carbon nanotubes can be prepared by mixing them with raw materials such as organic resin polymers according to conventional preparation methods to obtain a CNT conductive heating film, which well solves the problems of agglomeration and dispersion of graphitized carbon nanotubes, has excellent heating performance, and is very suitable for use in thermal insulation products.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a CNT conductive heating film, the method comprising the following steps:
[0006] (1) melt-mixing a first thermoplastic polyurethane elastomer and modified graphitized carbon nanotubes in a mass ratio of 80-85:15-20, coating, and naturally cooling to room temperature to obtain a film layer;
[0007] (2) mixing the second thermoplastic polyurethane elastomer, the insulating agent and N,N-dimethylformamide in a mass ratio of 10:0.2-0.3:80-100 at 60-80° C. under ultrasonic stirring for 6-12 h to obtain a membrane liquid;
[0008] (3) Apply the membrane liquid to one side of the membrane layer and dry it, and the preparation is completed.
[0009] As a preferred technical solution of the present invention, the modified graphitized carbon nanotubes in step (1) are prepared by the following steps:
[0010] Step A: adding 1-1.2 parts by weight of pretreated graphitized carbon nanotubes and 8-10 parts by weight of ethylenediamine to 40-50 parts by weight of N,N-dimethylformamide, stirring and mixing in ultrasound at 55-60° C. for 40-48 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 40-80° C. until constant weight, to obtain component A;
[0011] Step B: adding 1-1.5 parts by weight of component A to 50-70 parts by weight of deionized water, and then stirring and mixing for 15-30 minutes in ultrasound at room temperature to obtain component B;
[0012] Step C: adding 0.5-1 parts by weight of carboxymethyl chitosan to 35-40 parts by weight of deionized water, and then stirring and mixing at 30-40° C. for 10-15 minutes in ultrasonication to obtain component C;
[0013] Step D: adding the component C and 0.2-0.3 parts by weight of 1,2,7,8-diepoxyoctane dropwise to the component B at 70-80° C. while stirring, and continuing to stir at a constant temperature for 6-8 hours after all the addition is completed, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 40-80° C. until constant weight, to obtain component D;
[0014] Step E: adjusting the pH of 60-80 parts by weight of ethanol aqueous solution to 3-3.5 with aqueous hydrochloric acid solution, then adding the component D and 0.2-0.3 parts by weight of aniline, and then dropping 8-10 parts by weight of 10% ammonium persulfate aqueous solution while stirring in an ice bath and ultrasound, and after all the addition is completed, continue to stir at a constant temperature for 4-6 hours, let stand for 4-6 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 40-80° C. until constant weight, and the preparation is completed.
[0015] Furthermore, the pretreated graphitized carbon nanotubes in step A are prepared by the following steps:
[0016] 0.8-1 parts by weight of graphitized carbon nanotubes are added to 60-80 parts by weight of a 37% hydrochloric acid aqueous solution, and then stirred for 1-2 hours in an ultrasonic state with a power of 300-500 W at room temperature, filtered, and the filter residue is washed with deionized water, and finally vacuum dried at 40-80° C. until constant weight, and the preparation is completed.
[0017] Furthermore, the power of the ultrasound in step A is 300-500W.
[0018] Furthermore, the power of the ultrasound in step B is 300-500W.
[0019] Furthermore, the power of the ultrasound in step C is 300-500W.
[0020] Furthermore, in step D, the dropping rate of component C is controlled at 2-3s / drop.
[0021] Furthermore, the dropping rate of the 1,2,7,8-diepoxyoctane in step D is controlled at 5s / drop.
[0022] Furthermore, the mass fraction of the hydrochloric acid aqueous solution in step E is 37%.
[0023] Furthermore, the mass fraction of the ethanol aqueous solution in step E is 80-90%.
[0024] Furthermore, the power of the ultrasound in step E is 300-500W.
[0025] Furthermore, the dripping rate in step E is controlled at 3-5s / drop.
[0026] As a preferred technical solution of the present invention, the melt mixing in step (1) refers to mixing by stirring at 190-200° C. for 10-15 minutes.
[0027] As a preferred technical solution of the present invention, the insulating agent in step (2) is nano-silicon dioxide.
[0028] As a preferred technical solution of the present invention, the power of the ultrasound in step (2) is 300-500W.
[0029] As a preferred technical solution of the present invention, the drying in step (3) refers to vacuum drying at 85-90°C for 1 hour.
[0030] A CNT conductive heating film prepared by the preparation method as described above.
[0031] An application of a CNT conductive heating film, wherein the CNT conductive heating film is applied to thermal insulation products.
[0032] Beneficial effects of the present invention:
[0033] (1) The present invention creatively uses ethylenediamine to modify the surface of graphitized carbon nanotubes that have been pretreated with hydrochloric acid with amino groups, thereby obtaining component A, and then uses 1,2,7,8-diepoxyoctane as a cross-linking agent, based on the bonding effect of epoxy groups and amino groups, cross-linking and coating the surface of component A with carboxymethyl chitosan containing amino groups to form a first coating layer, and then adds aniline as a modifier, and constructs a second coating layer based on in situ polymerization, thereby obtaining modified graphitized carbon nanotubes, which can be prepared by conventional preparation methods with raw materials such as organic resin polymers to obtain a CNT conductive heating film, which effectively solves the problems of agglomeration and dispersibility of graphitized carbon nanotubes, has excellent heating performance, and is very suitable for use in thermal insulation products.
[0034] (2) The present invention creatively coats graphitized carbon nanotubes with organic polymers twice, namely, surface crosslinking of carboxymethyl chitosan and in-situ polymerization of aniline, thereby forming a three-layer composite structure of graphitized carbon nanotubes / carboxymethyl chitosan / polyaniline, and obtaining a modified graphitized carbon nanotube, which gives the obtained CNT conductive heating film excellent heating performance and effectively solves the problems of agglomeration and dispersion of graphitized carbon nanotubes in the organic resin polymer matrix. On the one hand, the crosslinking of carboxymethyl chitosan affects the electron cloud distribution on the surface of the graphitized carbon nanotubes, thereby enhancing the carbon element activity of the graphitized carbon nanotubes, increasing the resistance, and obtaining a better heating effect. On the other hand, aniline is converted into polyaniline after in-situ polymerization, which has strong conductivity and can promote the establishment of a good conductive network between each modified graphitized carbon nanotube, thereby improving the overall heating efficiency. At the same time, after coating the graphitized carbon nanotubes as an organic polymer, it can improve the interface compatibility, reduce the occurrence of agglomeration, and promote the uniform dispersion of the modified graphitized carbon nanotubes.
[0035] (3) The present invention creatively coats graphitized carbon nanotubes twice to prepare a modified graphitized carbon nanotube. During the coating process, although carboxymethyl chitosan is also an organic polymer and can play a role in improving interface compatibility, it cannot achieve good technical effects when used as the "outermost layer". The possible reason is that it will hinder the continuity of the conductive path and make it difficult to achieve efficient heat generation. Only when used as the "middle layer" can the three play an excellent synergistic effect. DETAILED DESCRIPTION
[0036] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.
[0037] The graphitized carbon nanotubes in all the embodiments and comparative examples of the present invention were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. and were numbered XFM46; the carboxymethyl chitosan was purchased from Jinan Xinzhiyuan Biotechnology Co., Ltd.; the first thermoplastic polyurethane elastomer was purchased from Bayer, Germany, with model 95A; the second thermoplastic polyurethane elastomer was purchased from Wanhua Chemical Group Co., Ltd., with model WHT-1185EC; nano-silica was purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., with model XT-SI02-02; the thickness of the CNT conductive heating film was 100 μm; the thickness of the film layer was 70 μm.
[0038] Example 1
[0039] A method for preparing a CNT conductive heating film, the method comprising the following steps:
[0040] (1) melt-mixing a first thermoplastic polyurethane elastomer and a modified graphitized carbon nanotube in a mass ratio of 80:15, coating, and naturally cooling to room temperature to obtain a film layer;
[0041] (2) mixing the second thermoplastic polyurethane elastomer, the insulating agent and N,N-dimethylformamide in a mass ratio of 10:0.2:80 under ultrasonic stirring at 60° C. for 6 h to obtain a membrane liquid;
[0042] (3) Apply the membrane liquid to one side of the membrane layer and dry it, and the preparation is completed.
[0043] The modified graphitized carbon nanotubes in step (1) are prepared by the following steps:
[0044] Step A: adding 1 part by weight of pretreated graphitized carbon nanotubes and 8 parts by weight of ethylenediamine to 40 parts by weight of N,N-dimethylformamide, stirring and mixing in ultrasound at 55°C for 40 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 40°C until constant weight, to obtain component A;
[0045] Step B: adding 1 part by weight of component A to 50 parts by weight of deionized water, and then stirring and mixing for 15 minutes under ultrasound at room temperature to obtain component B;
[0046] Step C: adding 0.5 parts by weight of carboxymethyl chitosan to 35 parts by weight of deionized water, and then stirring and mixing at 30° C. for 10 minutes in ultrasonication to obtain component C;
[0047] Step D: adding the component C and 0.2 parts by weight of 1,2,7,8-diepoxyoctane dropwise to the component B at 70° C. while stirring, and continuing to stir at a constant temperature for 6 hours after all the additions are completed, filtering, taking the filter residue, washing it with deionized water, and finally drying it under vacuum at 40° C. until constant weight, to obtain component D;
[0048] Step E: The pH value of 60 parts by weight of ethanol aqueous solution is adjusted to 3 with aqueous hydrochloric acid solution, and then the component D and 0.2 parts by weight of aniline are added, and then 8 parts by weight of 10% ammonium persulfate aqueous solution is added dropwise while stirring in ultrasound under an ice bath, and after all the addition is completed, the mixture is stirred at a constant temperature for 4 hours, allowed to stand for 4 hours, filtered, the filter residue is taken, washed with deionized water, and finally vacuum dried at 40° C. until constant weight, and the preparation is completed.
[0049] The pretreated graphitized carbon nanotubes in step A are prepared by the following steps:
[0050] 0.8 parts by weight of graphitized carbon nanotubes were added to 60 parts by weight of a 37% hydrochloric acid aqueous solution, and then the mixture was stirred for 1 h in an ultrasonic bath with a power of 300 W at room temperature, filtered, and the residue was washed with deionized water, and finally vacuum dried at 40° C. until constant weight, and the preparation was completed.
[0051] The power of the ultrasound in step A is 300W.
[0052] The power of the ultrasound in step B is 300W.
[0053] The power of the ultrasound in step C is 300W.
[0054] In step D, the dropping rate of component C is controlled at 2s / drop.
[0055] The dropping rate of 1,2,7,8-diepoxyoctane in step D is controlled at 5s / drop.
[0056] The mass fraction of the hydrochloric acid aqueous solution in step E is 37%.
[0057] The mass fraction of the ethanol aqueous solution in step E is 80%.
[0058] The power of the ultrasound in step E is 300W.
[0059] The rate of the dropping in step E is controlled at 3s / drop.
[0060] The melt mixing in step (1) refers to mixing by stirring at 190° C. for 10 minutes.
[0061] The insulating agent in step (2) is nano-silicon dioxide.
[0062] The power of the ultrasound in step (2) is 300W.
[0063] The drying in step (3) refers to vacuum drying at 85° C. for 1 h.
[0064] A CNT conductive heating film prepared by the preparation method as described above.
[0065] An application of a CNT conductive heating film, wherein the CNT conductive heating film is applied to thermal insulation products.
[0066] Example 2
[0067] A method for preparing a CNT conductive heating film, the method comprising the following steps:
[0068] (1) melt-mixing a first thermoplastic polyurethane elastomer and a modified graphitized carbon nanotube in a mass ratio of 85:20, coating, and naturally cooling to room temperature to obtain a film layer;
[0069] (2) mixing the second thermoplastic polyurethane elastomer, the insulating agent and N,N-dimethylformamide in a mass ratio of 10:0.3:100 at 80° C. under ultrasonic stirring for 12 h to obtain a membrane liquid;
[0070] (3) Apply the membrane liquid to one side of the membrane layer and dry it, and the preparation is completed.
[0071] The modified graphitized carbon nanotubes in step (1) are prepared by the following steps:
[0072] Step A: adding 1.2 parts by weight of pretreated graphitized carbon nanotubes and 10 parts by weight of ethylenediamine to 50 parts by weight of N,N-dimethylformamide, stirring and mixing in ultrasound at 60°C for 48 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 80°C until constant weight, to obtain component A;
[0073] Step B: adding 1.5 parts by weight of component A to 70 parts by weight of deionized water, and then stirring and mixing for 30 minutes under ultrasound at room temperature to obtain component B;
[0074] Step C: adding 1 part by weight of carboxymethyl chitosan to 40 parts by weight of deionized water, and then stirring and mixing at 40° C. for 15 minutes in ultrasonication to obtain component C;
[0075] Step D: adding the component C and 0.3 parts by weight of 1,2,7,8-diepoxyoctane dropwise to the component B at 80° C. while stirring, and continuing to stir at a constant temperature for 8 hours after all the additions are completed, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 80° C. until constant weight, to obtain component D;
[0076] Step E: Using hydrochloric acid aqueous solution to adjust the pH of 80 parts by weight of ethanol aqueous solution to 3.5, then add the component D and 0.3 parts by weight of aniline, and then add 10 parts by weight of 10% ammonium persulfate aqueous solution dropwise while stirring in an ice bath and ultrasound, and after all the addition is completed, continue to stir at a constant temperature for 6 hours, let it stand for 6 hours, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 80°C until constant weight, and the preparation is completed.
[0077] The pretreated graphitized carbon nanotubes in step A are prepared by the following steps:
[0078] 1 part by weight of graphitized carbon nanotubes was added to 80 parts by weight of a 37% hydrochloric acid aqueous solution, and then the mixture was stirred for 2 h in an ultrasonic bath with a power of 500 W at room temperature, filtered, and the residue was washed with deionized water, and finally vacuum dried at 80° C. until constant weight was achieved.
[0079] The power of the ultrasound in step A is 500W.
[0080] The power of the ultrasound in step B is 500W.
[0081] The power of the ultrasound in step C is 500W.
[0082] In step D, the dropping rate of component C is controlled at 3s / drop.
[0083] The dropping rate of 1,2,7,8-diepoxyoctane in step D is controlled at 5s / drop.
[0084] The mass fraction of the hydrochloric acid aqueous solution in step E is 37%.
[0085] The mass fraction of the ethanol aqueous solution in step E is 90%.
[0086] The power of the ultrasound in step E is 500W.
[0087] The rate of the dropping in step E is controlled at 5s / drop.
[0088] The melt mixing in step (1) refers to mixing by stirring at 200° C. for 15 minutes.
[0089] The insulating agent in step (2) is nano-silicon dioxide.
[0090] The power of the ultrasound in step (2) is 500W.
[0091] The drying in step (3) refers to vacuum drying at 90° C. for 1 h.
[0092] A CNT conductive heating film prepared by the preparation method as described above.
[0093] An application of a CNT conductive heating film, wherein the CNT conductive heating film is applied to thermal insulation products.
[0094] Example 3
[0095] A method for preparing a CNT conductive heating film, the method comprising the following steps:
[0096] (1) melt-mixing a first thermoplastic polyurethane elastomer and a modified graphitized carbon nanotube in a mass ratio of 83:18, coating, and naturally cooling to room temperature to obtain a film layer;
[0097] (2) mixing the second thermoplastic polyurethane elastomer, the insulating agent and N,N-dimethylformamide in a mass ratio of 10:0.25:90 under ultrasonic stirring at 70° C. for 8 h to obtain a membrane liquid;
[0098] (3) Apply the membrane liquid to one side of the membrane layer and dry it, and the preparation is completed.
[0099] The modified graphitized carbon nanotubes in step (1) are prepared by the following steps:
[0100] Step A: adding 1.1 parts by weight of pretreated graphitized carbon nanotubes and 9 parts by weight of ethylenediamine to 45 parts by weight of N,N-dimethylformamide, and then stirring and mixing under ultrasound at 58° C. for 45 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60° C. until constant weight, to obtain component A;
[0101] Step B: adding 1.3 parts by weight of component A to 60 parts by weight of deionized water, and then stirring and mixing for 20 minutes under ultrasound at room temperature to obtain component B;
[0102] Step C: adding 0.8 parts by weight of carboxymethyl chitosan to 38 parts by weight of deionized water, and then stirring and mixing at 35° C. for 13 minutes in ultrasound to obtain component C;
[0103] Step D: adding the component C and 0.25 parts by weight of 1,2,7,8-diepoxyoctane dropwise to the component B at 75° C. while stirring, and continuing to stir at a constant temperature for 7 hours after all the additions are completed, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 60° C. until constant weight, to obtain component D;
[0104] Step E: The pH value of 70 parts by weight of the ethanol aqueous solution is adjusted to 3.3 with an aqueous hydrochloric acid solution, and then the component D and 0.25 parts by weight of aniline are added, and then 9 parts by weight of a 10% ammonium persulfate aqueous solution is added dropwise while stirring in an ice bath and ultrasound. After all the additions are completed, the mixture is stirred at a constant temperature for 5 hours, allowed to stand for 5 hours, filtered, and the residue is taken, washed with deionized water, and finally dried in a vacuum at 60° C. until constant weight is reached, and the preparation is completed.
[0105] The pretreated graphitized carbon nanotubes in step A are prepared by the following steps:
[0106] 0.9 parts by weight of graphitized carbon nanotubes were added to 70 parts by weight of a 37% hydrochloric acid aqueous solution, and then the mixture was stirred for 1.5 hours in an ultrasonic bath with a power of 400 W at room temperature, filtered, and the residue was washed with deionized water, and finally vacuum dried at 70° C. until constant weight, and the preparation was completed.
[0107] The power of the ultrasound in step A is 400W.
[0108] The power of the ultrasound in step B is 400W.
[0109] The power of the ultrasound in step C is 400W.
[0110] In step D, the dropping rate of component C is controlled at 2.5 s / drop.
[0111] The dropping rate of 1,2,7,8-diepoxyoctane in step D is controlled at 5s / drop.
[0112] The mass fraction of the hydrochloric acid aqueous solution in step E is 37%.
[0113] The mass fraction of the ethanol aqueous solution in step E is 85%.
[0114] The power of the ultrasound in step E is 400W.
[0115] The rate of the dropping in step E is controlled at 4s / drop.
[0116] The melt mixing in step (1) refers to mixing by stirring at 195° C. for 13 minutes.
[0117] The insulating agent in step (2) is nano-silicon dioxide.
[0118] The power of the ultrasound in step (2) is 400W.
[0119] The drying in step (3) refers to vacuum drying at 88° C. for 1 h.
[0120] A CNT conductive heating film prepared by the preparation method as described above.
[0121] An application of a CNT conductive heating film, wherein the CNT conductive heating film is applied to thermal insulation products.
[0122] Comparative Example 1
[0123] Based on Example 3, step E is not performed, and the rest remain unchanged.
[0124] Comparative Example 2
[0125] On the basis of Example 3, step B, step C, step D and step E are not performed, and the rest remain unchanged.
[0126] Comparative Example 3
[0127] On the basis of Example 3, step B is omitted, and step D is changed to using hydrochloric acid aqueous solution (mass fraction of 37%) to adjust the pH of 70 parts by weight of ethanol aqueous solution (mass fraction of 85%) to 3.3, then add 1.3 parts by weight of component A and 0.25 parts by weight of aniline, and then add dropwise (the rate of dropwise addition is controlled at 4s / drop) 9 parts by weight of 10% ammonium persulfate aqueous solution under ultrasound (power of 400W) in an ice bath while stirring, and after all the dropwise addition is completed, continue to stir and mix at a constant temperature for 5h, let stand for 5h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60°C until constant weight, to obtain component Step E is changed to adding the component D to 60 parts by weight of deionized water, and then stirring for 20 minutes in ultrasound (power of 400 W) at room temperature to obtain component E, and adding the component C and 0.25 parts by weight of 1,2,7,8-diepoxyoctane dropwise to the component E at 75°C while stirring (the dropping rate of component C is controlled at 2.5s / drop, and the dropping rate of 1,2,7,8-diepoxyoctane is controlled at 5s / drop), and after all the dropwise addition is completed, stirring and mixing at a constant temperature for 7h, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60°C until constant weight, that is, the preparation is completed; the rest remains unchanged.
[0128] Comparative Example 4
[0129] On the basis of Example 3, step C, step D and step E are not performed, and step B is changed to using hydrochloric acid aqueous solution (mass fraction of 37%) to adjust the pH of 70 parts by weight of ethanol aqueous solution (mass fraction of 85%) to 3.3, then add 1.3 parts by weight of component A and 0.25 parts by weight of aniline, and then add dropwise (the dropping rate is controlled at 4s / drop) 9 parts by weight of 10% ammonium persulfate aqueous solution while stirring in ultrasound (power of 400W) under an ice bath, and after all the addition is completed, continue to stir and mix at a constant temperature for 5h, let stand for 5h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60°C until constant weight, that is, the preparation is completed; the rest remains unchanged.
[0130] Test Example 1
[0131] Heating performance test:
[0132] The CNT conductive heating films prepared in Example 3 and Comparative Examples 1-4 were respectively attached with conductive copper tapes, and then powered on at 36 V for 80 s (at room temperature), and the temperature after power-on was recorded (rounded to an integer).
[0133] Table 1. Heating performance test results
[0134] Temperature / ℃ Example 3 66 Comparative Example 1 52 Comparative Example 2 48 Comparative Example 3 57 Comparative Example 4 59
[0135] Comparison between Example 3 and Comparative Examples 1-4 shows that:
[0136] The difference between Comparative Example 1 and Example 3 is that the modified graphitized carbon nanotubes are a graphitized carbon nanotube / carboxymethyl chitosan composite structure.
[0137] The difference between Comparative Example 2 and Example 3 is that the modified graphitized carbon nanotubes do not form a composite structure.
[0138] The difference between Comparative Example 3 and Example 3 is that the modified graphitized carbon nanotubes are a graphitized carbon nanotube / polyaniline / carboxymethyl chitosan composite structure.
[0139] The difference between Comparative Example 4 and Example 3 is that the modified graphitized carbon nanotubes are a graphitized carbon nanotube / polyaniline composite structure.
[0140] From the comparison between Example 3 and Comparative Examples 1-4 in Test Example 1, it can be seen that the CNT conductive heating film prepared by the present invention has excellent heating performance.
[0141] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a CNT conductive heating film, characterized in that: The preparation method comprises the following steps: (1) melt-mixing a first thermoplastic polyurethane elastomer and modified graphitized carbon nanotubes in a mass ratio of 80-85:15-20, coating, and naturally cooling to room temperature to obtain a film layer; (2) mixing the second thermoplastic polyurethane elastomer, the insulating agent and N,N-dimethylformamide in a mass ratio of 10:0.2-0.3:80-100 at 60-80° C. under ultrasonic stirring for 6-12 h to obtain a membrane liquid; (3) Apply the membrane liquid to one side of the membrane layer and dry it, and the preparation is completed.
2. The method for preparing a CNT conductive heating film according to claim 1, characterized in that: The modified graphitized carbon nanotubes in step (1) are prepared by the following steps: Step A: adding 1-1.2 parts by weight of pretreated graphitized carbon nanotubes and 8-10 parts by weight of ethylenediamine to 40-50 parts by weight of N,N-dimethylformamide, stirring and mixing in ultrasound at 55-60° C. for 40-48 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 40-80° C. until constant weight, to obtain component A; Step B: adding 1-1.5 parts by weight of component A to 50-70 parts by weight of deionized water, and then stirring and mixing for 15-30 minutes in ultrasound at room temperature to obtain component B; Step C: adding 0.5-1 parts by weight of carboxymethyl chitosan to 35-40 parts by weight of deionized water, and then stirring and mixing at 30-40° C. for 10-15 minutes in ultrasonication to obtain component C; Step D: adding the component C and 0.2-0.3 parts by weight of 1,2,7,8-diepoxyoctane dropwise to the component B at 70-80° C. while stirring, and continuing to stir at a constant temperature for 6-8 hours after all the addition is completed, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 40-80° C. until constant weight, to obtain component D; Step E: adjusting the pH of 60-80 parts by weight of ethanol aqueous solution to 3-3.5 with aqueous hydrochloric acid solution, then adding the component D and 0.2-0.3 parts by weight of aniline, and then dropping 8-10 parts by weight of 10% ammonium persulfate aqueous solution while stirring in an ice bath and ultrasound, and after all the addition is completed, continue to stir at a constant temperature for 4-6 hours, let stand for 4-6 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 40-80° C. until constant weight, and the preparation is completed.
3. The method for preparing a CNT conductive heating film according to claim 2, characterized in that: The pretreated graphitized carbon nanotubes in step A are prepared by the following steps: 0.8-1 parts by weight of graphitized carbon nanotubes are added to 60-80 parts by weight of a 37% hydrochloric acid aqueous solution, and then stirred for 1-2 hours in an ultrasonic state with a power of 300-500 W at room temperature, filtered, and the filter residue is washed with deionized water, and finally vacuum dried at 40-80° C. until constant weight, and the preparation is completed.
4. The method for preparing a CNT conductive heating film according to claim 2, characterized in that: The mass fraction of the hydrochloric acid aqueous solution in step E is 37%.
5. The method for preparing a CNT conductive heating film according to claim 2, characterized in that: The mass fraction of the ethanol aqueous solution in step E is 80-90%.
6. The method for preparing a CNT conductive heating film according to claim 1, characterized in that: The melt mixing in step (1) refers to mixing by stirring at 190-200° C. for 10-15 minutes.
7. The method for preparing a CNT conductive heating film according to claim 1, characterized in that: The insulating agent in step (2) is nano-silicon dioxide.
8. The method for preparing a CNT conductive heating film according to claim 1, characterized in that: The drying in step (3) refers to vacuum drying at 85-90° C. for 1 h.
9. A CNT conductive heating film prepared by the preparation method as described in any one of claims 1 to 8.
10. An application of a CNT conductive heating film prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The CNT conductive heating film is used in thermal insulation products.
Citation Information
Patent Citations
Flexible electric heating film heating layer and preparation method thereof
CN112566290A
Conductive film, preparation method thereof and heating film
CN117202419A
Carbon nanotube heating film and preparation method thereof
CN117320203A
Film heater and manufacturing method of thereof
KR101436594B1